Looking at children : an introduction to child development - Bjorklund, David F.; Bjorklund, Barbara R. (Pacific Grove, Calif. : Brooks/Cole Pub. Co., 1992)
Written for students taking courses in child and adolescent development or developmental psychology, this text presents child development in a straightforward manner that stresses the uniqueness of every child.
Includes bibliographical references and indexes.
Keywords: Child development